Smart power plug for indoor information system - Yang, Huan (2015)
With the revolution of communication technology, especially wireless communication technology, the IB (intelligent building), smart home system have been rapidly developed from concept to practice. Now, the smart home system (or home automation system) has been more and more rapidly applied in ordinary family. For adapting to the market, it is necessary to develop a low-cost and high-efficient smart plug for HAS. The main objective of this project is redesign a smart plug based on HAS (Home Automation System), so that it can collect current information of the household appliances plugged in the smart plug and control the on-off of the power supply by remote devices such as smart phones. This report put forward to a hardware architecture of the smart plug that use ZigBee modules as the communication tools between the smart plug and smart gateway to transfer current information as well as control instructions. The first part of this report is the design process of the smart plug, including hardware design, components selection, design in Altium Designer, and programming process for MCU and XBee S2. The second part of this report is the demo and operation process of the smart plug. Additionally, this report discusses some typical application occasions in real life. Finally, the report gives the conclusion and discusses possible directions for future extensions.